A novel ex vivo protocol that mimics length and excitation changes of human muscles during walking induces force losses in EDL but not in soleus of mdx mice - Xiao Hu; Allison N. McCrady; Katherine E. Bukovec; Claire Yuan; Emily Y. Miller; Rachel K. Bour; Anthony C. Bruce; Katherine B. Crump; Shayn M. Peirce; Robert W. Grange; Silvia S. Blemker (PLoS ONE, 2025)
Although eccentric contraction protocols are widely used to study the pathophysiology and potential treatments for Duchenne muscular dystrophy (DMD), they do not reflect the stresses, strains, strain rates, and excitation profiles that DMD muscles experience during human daily functional tasks, like walking. This limitation of eccentric contractions may impede our understanding of disease progression in DMD and proper assessment of treatment efficacy. The goals of this study were to examine the extent of force loss induced by a gait cycling protocol we developed, and compare to that from a typical eccentric contraction protocol in soleus and extensor digitorum longus (EDL) muscles of mdx mice. To achieve this goal, mdx soleus and EDL muscles were subjected to eccentric contractions at three levels of strain (10%, 20% and 30% optimal length Lo) and up to 200 cycles of our gait cycling protocol that mimicked the length changes and excitation patterns of the corresponding muscles during human walking gait. Our results showed that EDL but not soleus muscles had significant losses in isometric tetanic forces after the cycling protocols. Compared to the eccentric contraction protocol, the decrements in contractile performance from the cycling protocol were similar to those from the eccentric contractions at 10% in soleus and 20% Lo in EDL. Together, these results indicated the gait cycling protocol is a valuable experimental approach to better understand disease progression and to screen and evaluate efficacy of novel therapeutics for DMD.